Proceedings of the 2018 Conference of the North American Chapter Of the Association for Computational Linguistics: Hu 2018
DOI: 10.18653/v1/n18-1163
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Egregious Conversations between Customers and Virtual Agents

Abstract: Virtual agents are becoming a prominent channel of interaction in customer service. Not all customer interactions are smooth, however, and some can become almost comically bad. In such instances, a human agent might need to step in and salvage the conversation. Detecting bad conversations is important since disappointing customer service may threaten customer loyalty and impact revenue. In this paper, we outline an approach to detecting such egregious conversations, using behavioral cues from the user, pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Based on these limitations, our proposed solution is to apply data programming to generate training data by using heuristic weak supervision strategies. We combine our domain heuristics to design a set of simple rule-based labeling functions [27,28] to generate online training labels. Once large-scale training data is generated, the goal is to compare heuristic performance with proposed models to see if models can learn beyond these simple rules.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on these limitations, our proposed solution is to apply data programming to generate training data by using heuristic weak supervision strategies. We combine our domain heuristics to design a set of simple rule-based labeling functions [27,28] to generate online training labels. Once large-scale training data is generated, the goal is to compare heuristic performance with proposed models to see if models can learn beyond these simple rules.…”
Section: Methodsmentioning
confidence: 99%
“…One recent work proposed a query representation learning technique with intent-sensitive word embeddings, and showed that modifications to improve query representation can improve overall model performance [16]. Another recent work introduced a model that can detect egregious conversations using textual representations, and addressed how this technique can be applied to an automated evaluation scheme [28]. There have been studies to predict causes of query reformulation in intelligent assistants by using system, acoustic, language and additional features [29].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…As these systems became more sophisticated, many work proposed new ideas to automate the evaluation process by predicting conversational user satisfaction, as defined in [28][29][30]. For instance, there have been successful attempts to predict satisfaction once conversations (sessions) are completed, using traditional methods [17,22] and neural-based models [13,14]. Lastly, one recent work [5] proposed a unified neural framework to predict offline (sessionlevel) and online (turn-level) satisfaction simultaneously.…”
Section: Background and Related Workmentioning
confidence: 99%